Hots (Higher Order Thinking Skill) in Reading Exercise - Zaharil Anasy (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract The objective of this study is to get empirical evidence of the distribution of the higher order thinking skill based on the revised edition of Bloom’s Taxonomy in the essay question of the reading exercises in “Pathway to English textbook” for the 11th grade of senior high school student.This study uses the content analysis method to identify specified characteristics of the material in the textbook. The data of essay reading questions are collected by using “Pathway to English textbook” and the analysis card as the data sources and the checklist table. The writer finds that the distribution of the higher order thinking level is lower than the lower order thinking level. The data also shows that the distribution of the higher order thinking skill in the essay reading questions in the Pathway to English textbook is unequal. It doesn’t treat the higher order thinking skill properly, particularly the create skill which doesn’t exist in the essay reading questions. It only gives more emphasis on the analyzed skill by obtaining the highest number among the three skills in the higher order thinking level. Abstrak Tujuan penelitian ini adalah untuk mendapatkan bukti empiris distribusi keterampilan berpikir tingkat tinggi berdasarkan Taksonomi Bloom edisi revisi dalam pertanyaan esai latihan membaca